Management of women with mild and moderate cervical dyskaryosis - Flannelly, G; Anderson, D; Kitchener, H C; Mann, E M F; Campbell, M; Fisher, P; Walker, F; Templeton, A A (BMJ, 1994)
Abstract Objective : To compare the outcomes in women with mild and moderate dyskaryosis after increasing periods of surveillance and thereby to define a rational protocol for managing such women. Design - Prospective study with randomisation of women to one of four treatment groups, each with a different period of surveillance; one group in which the women were given immediate treatment and three other groups in which the women were under surveillance for six, 12, and 24 months. Setting : A dedicated colposcopy clinic in Aberdeen, Scotland. Subjects : 902 women who presented with a mildly or moderately dyskaryotic smear for the first time. Interventions : Cytological and colposcopic examinations at intervals of six months until the allocated period of surveillance was completed, at which time biopsy was performed. Women with severe dyskaryosis were withdrawn from surveillance and a biopsy was performed. Main outcome measures - The histological findings after punch biopsy or large loop excision of the transformation zone, and the trends in cytological appearances of serial cervical smears. Results - 793 women completed the study. In all, 769 women had an adequate final smear, of which 197 were normal cytologically, 328 were still mildly or moderately dyskaryotic, and 244 were severely dyskaryotic. Seventeen of the 67 (25%) women with one repeat smear showing non-dyskaryosis had cervical intraepithelial neoplasia grade III compared with only one of the 31 (3%) women with no dyskaryosis in four repeat cervical smears (P <0.0001). None of the women had invasive cancer. Of 158 women whose index smear showed mild dyskaryosis and who were allocated to the group under surveillance for two years, only 40 had not defaulted or still had dyskaryotic smears by the end of the two years. Conclusion : Cytological surveillance, although safe, is not an efficient strategy for managing women with mildly abnormal smears. Women with any degree of dyskaryosis in a smear should be referred for colpscopy.